(3GdeSDhdjg GdeOjfI GdfGTFI Yf MhGOK GdSjGQGJ (B((3OQGSI ebGQfI(B)s - (3NGdO eUWai(B, (3agejs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2005)
(3MbjbI YbO GdJCejf GdGLHGQj, CMcGe GdNWQ aj GdJCejf GdGLHGQj, UGMH GdMb aj GdJYhjV, GdCSGS GdbGfhfj ddOYhi GdeHGTQI, QLhY GdeDef Ydi GdZjQ GdeSDhd(B.s
(3GdeQGLY U(B.169s
Keywords: (3GdJCejfGJ(B- (3bhGfjf hJTQjYGJs; (3GdJYhjVGJs; (3GdYbhOs; (3GdbGfhf GdeOfjs